Tolerance Stack Analysis in Francis Turbine Design - Djodikusumo, Indra; Suherman, Koko; Oken, Paskalis Bowo A. (ITB Journal Publisher, LPPM ITB, 2010)
TheÂ toleranceÂ stackingÂ problemÂ arisesÂ inÂ theÂ contextÂ ofÂ assemblies fromÂ interchangeableÂ partsÂ becauseÂ ofÂ theÂ inabilityÂ toÂ produceÂ orÂ toÂ joinÂ parts exactlyÂ accordingÂ toÂ nominalÂ dimensions.Â EitherÂ theÂ relevantÂ partâsÂ dimension varies around some nominal valuesÂ from part to part or the act of assembly that leadsÂ toÂ variation.Â ForÂ example,Â asÂ runnerÂ ofÂ FrancisÂ turbineÂ isÂ joinedÂ with turbine shaft via mechanical lock,Â there is not only variation in the diameter of runnerÂ and the concentricity between the runnerÂ holeÂ andÂ turbineÂ shaft, but also theÂ variation inÂ concentricityÂ betweenÂ theÂ outerÂ partsÂ ofÂ runnerÂ to runner hole. Thus,Â thereÂ isÂ theÂ possibilityÂ thatÂ theÂ assemblyÂ ofÂ suchÂ interactingÂ partsÂ wonât functionÂ orÂ wonâtÂ comeÂ togetherÂ asÂ planned.Â Â ResearchÂ inÂ thisÂ areaÂ hasÂ been conducted and 2 mini hydro Francis turbines (800 kW and 910 kW) have been designed and manufactured for San Sarino and Sawi Dago 2 in Central Sulawesi. ExperiencesÂ inÂ analyzingÂ theÂ toleranceÂ stacksÂ haveÂ beenÂ documented.Â InÂ this paper it will be demonstrated how the requirements of assembling performance are derived to be theÂ designedÂ Â Â tolerancesÂ of each interacting component, suchÂ a way that the assembling would be functioning and come together as planned.